Prarancangan Pabrik Fatty Alcohol Ethoxylate Dari Fatty Alcohol Dan Etilen Oksida Kapasitas 52.000 Ton/Tahun - Sa'adah, Nur; , Ir. Herry Purnama, M.T., Ph.D; , Kusmiyati, S.T., M.T., Ph.D (2016)
Surfactant industry needs increased with the growth of development in Indonesia. The increases od surfactant needed will increase the need for Fatty Alcohol ethoxylate (FAE), which is one of the ingredients in the manufacture of surfactants. Besides being used industrial surfactants, FAE is also used as an ingredient in cosmetics, pharmaceuticals and textiles. To fulfill domestic needs and their export opportunities that are still open, FAE factory is designed with a capacity of 50.000 tons/year. This factory will be established in Cilegon, Banten at 2020. Raw material for manufacturing FAE is fatty alcohol and ethylene oxide and potassium hydroxide (KOH) as catalyst. The process step is divided to 3 steps, there are activation catalyst, manufacturing product in reactor and purification product. First step, mixing fatty alcohol and KOH catalyst 0,5% weight of fatty alcohol at temperature of 180 °C in 30 minutes in the mixer. In this process, activation catalyst is happened. Second step, the solution is fed to bubble reactor and reacted with ethylene oxide at temperature of 180 °C and pressure 2 atm, this reaction is called ethoxylation. The conversion as long as manufacturing product in reactor is 84,43%. Last step, the product will be refined at distillation column, so the conversion will increase into 99,8%. From economic analysis shows Percent Return On Investment before tax = 41,37 %; Percent Return On Investment after tax = 31,03%, Pay Out Time before tax = 1,95 years; Pay Out Time after tax = 2,44 years. Break Even Point (BEP) = 41,84%; Shut Down Point (SDP) = 20,75%, Discounted Cash Flow (DCF) = 38,64%. The conclusion from this economic analysis is the factory is feasible to established.